The Effects of Robot Programming on Mathematical Achievement, Mathematics Anxiety, and Programming Self-Efficacy - Hangun, Mehmet Emin; Turel, Yalin Kilic (Wiley, 2025)
Programming skills and mathematical thinking are among the important skills in the field of information technology. It is common knowledge that programming often involves topics such as loops, variables, functions and mathematical expressions. Students who are beginners in programming or who learn text-based programming are prone to assuming a negative attitude towards their programming education. The aim of this study is to examine the effect of using educational robots on students' mathematical achievement, mathematics anxiety and computer programming self-efficacy perception. 117 secondary school 6th grade students participated in the study, which was conducted in a quasi-experimental design. To compare the variables between the two groups in this study, an independent t-test was used. To analyze the corrected variance differences between the groups, a linear covariance (ANCOVA) analysis was done. At the end of the study, significant differences between the groups in terms of mathematics anxiety and programming self-efficacy perception were noted. In terms of mathematical achievement, however, although it increased both in the experimental group and the control group, no significant differences were found. When the mathematics anxiety pre-test score was controlled, ANCOVA analysis revealed that there was a significant difference in the mathematics anxiety Posttest. This study demonstrated that robots can be an effective tool for positive change in mathematics anxiety and self-efficacy perceptions in computer programming. However, although educational robots provided a positive change in math achievement, they did not provide a significant difference between the groups. At this point, long-term studies examining mathematics achievement with educational robots are needed.
Keywords: computer programming self-efficacy perception; educational robot; mathematical achievement; mathematics anxiety; robot programming